An isolated organ feasibility study of deformable self-assembled magnetic anastomosis rings for esophageal stenosis anastomosis - Miaomiao Zhang; Xuhe Zhao; Qiuye Zhong; Linxin Shen; Ruimin Gong; Yi Lyu; Xiaopeng Yan (Scientific Reports)
Abstract Magnetic compression anastomosis (MCA) for esophageal stenosis requires the insertion of magnets through two channels, transoral and transgastrostomy. Herein, we designed a Y-Z deformable self-assembled magnetic anastomosis ring (Y-Z DSAMAR) for esophageal stricture anastomosis through the transoral passage only. We introduce a Y-Z DSAMAR and verify its feasibility for single-access esophageal stenosis anastomosis in isolated organs. We procured esophagi from 10 pigs. Next, we ligated the middle part of these esophagi with 7 − 0 silk to prepare an esophageal stenosis model. The linear Y-Z DSAMAR completed the deformation self-assembly and transitioned from its initial linear shape to a circular one while passing through the esophageal stenosis. The operation time, the success rate of the deformation self-assembly of Y-Z DSAMARs, and the successful MCA for esophageal stenosis were recorded. We successfully obtained a trapezoidal magnetic unit. Ten such magnetic units can self-assemble into a ring after the hard guide wire is withdrawn. The success rates for both self-assembly deformation and esophageal stenosis anastomosis were 93.33%, while that for esophageal stenosis anastomosis with successful deformation was 100%. Y-Z DSAMARs exhibit remarkable deformation-controllable characteristics. Further optimization of the operational procedure and verification through animal experiments are needed before they can be clinically applied.